32 Does 'real-world' mechanical circulatory support match randomised controlled trials? The United Kingdom impella (Ukpella) registry. (17th July 2020) - Ryan, Matthew; O'Gallagher, Kevin; Vetrugno, Vincenzo; Thirunavukarasu, Sharmaine; Briceno, Natalia; Khan, Sohail Q; Clapp, Brian; Hendry, Cara; Webb, Ian; Townend, Jonathan; Al-Najjar, Yahya; Byrne, Jonathan; et al.
Abstract : Background: Impella utilisation is increasing but reimbursement and usage patterns vary significantly around the world. The National Institute for Health and Care Excellence (NICE) recently approved the use of Impella for high-risk percutaneous coronary intervention (PCI) in centres with specific expertise in the use of mechanical circulatory support and with specific arrangements for governance, audit and consent in place. Hypothesis: In the United Kingdom (UK), due to increased selection, Impel is used in higher-risk cases than in randomised controlled trials (RCT). Methods: All patients undergoing Impella implants between 2008 - 2019 in the four highest volume UK Impella centres (St. Thomas' Hospital and King's College Hospital, London; Queen Elizabeth Hospital, Birmingham; Manchester Royal Infirmary, Manchester) were included. Demographic, clinical, procedural and outcome data were extracted from electronic health records. Patients were stratified by the presence of cardiogenic shock at presentation. Pre-procedural characteristics and outcomes (30-day and 1-year all-cause mortality) were compared to the BCIS-1, PROTECT-2 and IABP-SHOCK2 trial cohorts respectively. Multivariate logistic regression analysis was used to identify independent predictors of complications. Continuous data are presented as mean ± SD or median (IQR) depending on normality. Results: Two-hundred and thirty-four patients were included. The indication was cardiogenic shock in 83 (35.5%) and high-risk PCI in 146 (62.4%); of the latter 58.9% had acute coronary syndromes and 41.1% were elective) and bailout in 2.1%. PCI was performed via femoral access in 55.6%. Patients undergoing high-risk PCI were older than those with cardiogenic shock (73.3 ± 10.8 years vs. 59.9 ± 14.0 years, p<0.001), as well as being more likely to have a history of previous myocardial infarction (52.1% vs. 26.3%, p<0.001), chronic kidney disease (24.7% vs. 13.9%, p=0.005) and peripheral vascular disease (17.1% vs. 6.3%, p=0.005). High-risk PCI patients in UKpella had a higher BCIS-Jeopardy Score, more left main disease and underwent more calcium modification but had a higher left ventricular ejection fraction than in RCTs. UKpella high-risk PCI 30-day and 1-year mortality was 16.4% and 30.7% respectively, significantly higher than in RCTs (Table 1 ). Cardiogenic shock patients in UKpella had a higher 30-day mortality than RCT patients (56.1% versus 40.5%, p = 0.034) but 1-year mortality was similar. Figure 1 demonstrates mortality over follow up. Major bleeding (Bleeding Academic Research Consortium scale 3-5) occurred in around 20% of both shock and high-risk PCI cases. Femoral access for PCI was related to the risk of bleeding in high-risk PCI (odds ratio 2.65 [1.04-6.74], p=0.040) but not in cardiogenic shock. Vascular complications occurred more frequently in shock than high-risk cases (13.6% vs. 9.0%). Figure 2 shows the rates of implants, bleeding and vascular complications. Conclusions: Patients selected for Impella in the UK are a group with a particularly adverse prognosis, in terms of baseline predictors of risk as well as higher short- and medium-term mortality than in RCTs. Bleeding and vascular complications occur in an important minority. Randomised clinical trials are required to define a population in whom the balance of benefit and risk is most favourable. Conflict of Interest: None